2012
DOI: 10.1002/jso.23031
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of dictated operative reports in breast cancer—the case for synoptic reporting

Abstract: The dictated operative report for breast cancer surgery does not adequately capture important data. A synoptic reporting system, which requires documentation of important elements, is a potentially beneficial tool in breast cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 10 publications
3
21
1
Order By: Relevance
“…Their quality audit reinforced these perceptions, as the 40 Roux‐en‐Y gastric bypass NRs they analyzed contained only 62% ± 6.6% of the variables deemed necessary for inclusion. This lack of completeness within NRs was also found in NRs for pancreatic surgery (72.5% completeness for pancreaticoduodenectomy), breast surgery (66% completeness), and upper limb surgery (71.1% completeness) . That fact that our study found a higher average QI inclusion rate (85%) compared to these other studies may reflect the greater emphasis placed on documentation at our institution.…”
Section: Discussionsupporting
confidence: 59%
“…Their quality audit reinforced these perceptions, as the 40 Roux‐en‐Y gastric bypass NRs they analyzed contained only 62% ± 6.6% of the variables deemed necessary for inclusion. This lack of completeness within NRs was also found in NRs for pancreatic surgery (72.5% completeness for pancreaticoduodenectomy), breast surgery (66% completeness), and upper limb surgery (71.1% completeness) . That fact that our study found a higher average QI inclusion rate (85%) compared to these other studies may reflect the greater emphasis placed on documentation at our institution.…”
Section: Discussionsupporting
confidence: 59%
“…Several studies report that SRs provide more complete information than the NRs. 4,[23][24][25][26][27] In other specialties, par ticularly in pathology, synoptic reporting has been widely embraced, which has improved interdisciplinary com munication and led to more effective coordination of clinical care for individual patients. [28][29][30] There is wide acceptance of SRs by clinicians who prefer the readability of SRs over NRs.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] There is wide acceptance of SRs by clinicians who prefer the readability of SRs over NRs. [27][28][29][30] Further structured synoptic reporting results promote quality by standardizing the reporting processes among patients and institutions. Several jurisdictions mandate the use of synoptic pathology reports as a performance indicator.…”
Section: Discussionmentioning
confidence: 99%
“…They describe the course of the operation as well as any abnormal findings in the surgical process. Template-based and structured methods exist for recording the operative note (DeOrio, 2002), and in many cases have been shown to increase the completeness of surgical information (Park et al, 2010;Gur et al, 2011;Donahoe et al, 2012). The use of natural language, however, is still preferred for its expressive power.…”
Section: Introductionmentioning
confidence: 99%